2021
DOI: 10.1017/s0030605320000605
|View full text |Cite
|
Sign up to set email alerts
|

The implications of vehicle collisions for the Endangered endemic Zanzibar red colobusPiliocolobus kirkii

Abstract: Roads affect wildlife in a variety of negative ways. Road ecology studies have mostly concentrated on areas in the northern hemisphere despite the potentially greater impact of roads on biodiversity in tropical habitats. Here, we examine 4 years (January 2016–December 2019) of opportunistic observations of mammalian roadkill along a road intersecting Jozani-Chwaka Bay National Park, Unguja, Zanzibar. In particular, we assess the impact of collisions on the population of an endemic primate, the Endangered Zanzi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…Other mitigations, such as signage and speed bumps, should be considered in urban areas under similar conditions. However, studies of their effectiveness for primates remain little studied as there are no qualitative analyses on signage to prevent primate‐vehicle collisions, and only one study on speed bumps (which found them effective) (Olgun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other mitigations, such as signage and speed bumps, should be considered in urban areas under similar conditions. However, studies of their effectiveness for primates remain little studied as there are no qualitative analyses on signage to prevent primate‐vehicle collisions, and only one study on speed bumps (which found them effective) (Olgun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…6000 individuals, 50% of which are found at this national park (Davenport et al, 2019 ). The subjects of this study are exposed to high levels of habitat disturbance and human activity from roads, tourism, and nearby villages and farms (Georgiev et al, 2019 ; Olgun et al, 2021 ; Siex & Struhsaker, 1999 ). They do not receive provisioned food.…”
Section: Methodsmentioning
confidence: 99%
“…Various strategies for mitigating WVCs are implemented across the globe and may include wildlife underpasses and bridges, fences, speed bumps to reduce traffic speed, and signage to warn drivers [91][92][93][94]. The effectiveness of a mitigation measure depends on a combination of variables, including the location, habitat type, road type, target species, and whether multiple strategies are implemented simultaneously [95].…”
Section: Mitigating Primate Roadkillmentioning
confidence: 99%